2007
DOI: 10.1111/j.1939-1676.2007.tb02945.x
|View full text |Cite
|
Sign up to set email alerts
|

Plethysmographic Comparison of Breathing Pattern in Heaves (Recurrent Airway Obstruction) Versus Experimental Bronchoconstriction or Hyperpnea in Horses

Abstract: Background: Horses with recurrent airway obstruction (heaves) are described as exhibiting ''increased abdominal effort,'' but it is unknown whether this translates to an effective contribution to ventilation.Hypothesis: We hypothesized that heaves is characterized by asynchrony between rib cage and abdominal motions, and that the abdominal component is the major contributor to ventilation.Animals: The rib cage versus abdominal motion in naturally occurring heaves (n 5 15) was compared to controls at rest (n 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 30 publications
4
29
0
1
Order By: Relevance
“…In the current study, horses averaged a tidal volume of 7.89 ± 1.43 L (mean ± stdev) and respiratory frequency of 12 bpm during eupnoeic respiration, which is similar to previous studies using ultrasound or Fleisch-type pneumotachometers [3235], and slightly greater than values determined by respiratory inductance plethysmography and pneumotachography [25, 36]. In addition to differences due to technique, it is possible that equipment differences, such as mask volume and airflow resistance, or physiological differences between horses, such as age [36], use [35] or sub-clinical airway disease [34, 35], may influence values determined during pulmonary function testing.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the current study, horses averaged a tidal volume of 7.89 ± 1.43 L (mean ± stdev) and respiratory frequency of 12 bpm during eupnoeic respiration, which is similar to previous studies using ultrasound or Fleisch-type pneumotachometers [3235], and slightly greater than values determined by respiratory inductance plethysmography and pneumotachography [25, 36]. In addition to differences due to technique, it is possible that equipment differences, such as mask volume and airflow resistance, or physiological differences between horses, such as age [36], use [35] or sub-clinical airway disease [34, 35], may influence values determined during pulmonary function testing.…”
Section: Discussionsupporting
confidence: 88%
“…Study horses exhibited PIF and PEF variably in early, middle and late phases of respiration in apparent random distribution. Although such variability is well documented [17] and previous studies have differed in their conclusions regarding normal resting respiratory patterns in horses [20, 32, 38], it has been suggested that normal horses typically have PEF early in expiration and PIF late in inspiration [25, 32, 33]. Expiratory flows have greater sensitivity and accuracy for the diagnosis of obstructive airway disease in human patients and horses [4], and both human and equine studies have demonstrated that PEF occurs earlier in expiration in individuals with airway obstruction [22, 39, 40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, increased tidal breathing peak expiratory flow has been reported in horses with recurrent airway obstruction (heaves). [37,38] Horses in the study by Petsche, et al also showed increased ratios of expiratory flows compared with expiratory flows later in expiration, as found in GRMD dogs. [37] Dogs with chronic bronchitis were reported to have greater PTEF:EF25 compared with control dogs, also consistent with our findings.…”
Section: Discussionmentioning
confidence: 95%
“…[33-38] For each dog, 8-10 tidal breaths representative of the predominant pattern were selected. Criteria for selection of breaths included: lack of artifacts, such as resulting from panting, sniffing, cough, or movement, on visual examination of the flow-time tracings; a difference of ≤5% between inspiratory and expiratory volumes, to exclude breaths with evidence of leaking of air from the mask; and, a respiratory frequency of ≤60 breaths per minute, to exclude panting.…”
Section: Methodsmentioning
confidence: 99%